Regime Switching in Inflation Targeting Under Conditions of Public Debt in the Philippines - Sotocinal, Noli R. (Philippine Management Review; Vol 22 (2015), 2015)
A standard inflation targeting framework assumes the absence of fiscal dominance, and abstracts from the effects of unbalanced fiscal positions and public debt financing. This assumption is relaxed by adding the notion of a fiscal gap into the standard inflation targeting model. The financing of fiscal gaps is assumed to be largely implemented through the creation or retirement of public debt, which then affects the premium levied on Philippine interest and exchange rates in the international and domestic capital markets. A Markovian Regime Switching Vector Autoregression model based on an extended inflation targeting system under the presence of a fiscal gap and public debt is specified and estimated using Philippine data. The research reveals that the fiscal gap significantly impacts on the target variables in the inflation targeting system and directly affects the short-term interest rate contrary to the standard assumption of zero fiscal dominance. Furthermore, there is evidence of the existence of interest rate regimes, such that activist fiscal policies in the low output regimes are only effective in the short term, as their impact on interest rates are larger and tend to lead to interest rate increases beyond those intended by the monetary authorities. The research’s findings support the notion that effective macroeconomic management requires some degree of policy coordination between the monetary and fiscal authorities.